Genomic and proteomic profiles of biofilms on microplastics are decoupled from artificial surface properties. (6th May 2021) - Oberbeckmann, Sonja; Bartosik, Daniel; Huang, Sixing; Werner, Johannes; Hirschfeld, Claudia; Wibberg, Daniel; Heiden, Stefan E.; Bunk, Boyke; Overmann, Jörg; Becher, Dörte; Kalinowski, Jörn; Schweder, Thomas; et al.
Summary: Microplastics in marine ecosystems are colonized by diverse prokaryotic and eukaryotic communities. How these communities and their functional profiles are shaped by the artificial surfaces remains broadly unknown. In order to close this knowledge gap, we set up an in situ experiment with pellets of the polyolefin polymer polyethylene (PE), the aromatic hydrocarbon polymer polystyrene (PS), and wooden beads along a coastal to estuarine gradient in the Baltic Sea, Germany. We used an integrated metagenomics/metaproteomics approach to evaluate the genomic potential as well as protein expression levels of aquatic plastic biofilms. Our results suggest that material properties had a minor influence on the plastic‐associated assemblages, as genomic and proteomic profiles of communities associated with the structurally different polymers PE and PS were highly similar, hence polymer‐unspecific. Instead, it seemed that these communities were shaped by biogeographic factors. Wood, on the other hand, induced the formation of substrate‐specific biofilms and served as nutrient source itself. Our study indicates that, while PE and PS microplastics may be relevant in the photic zone as opportunistic colonization grounds for phototrophic microorganisms, they appear not to be subject to biodegradation or serve as vectors for pathogenic microorganisms in marine habitats.